Resource (Light and Nitrogen) and Density-Dependence of Seaweed Growth - Xiao, Xi; Agusti, Susana; Lin, Fang; Xu, Caicai; Yu, Yan; Pan, Yaoru; Li, Ke; Wu, Jiaping; Duarte, Carlos M. (Frontiers in Marine Science, 2019)
Seaweed aquaculture is a rapidly growing component of marine food production, but the capacity to control seaweed growth lacks behind that of land agriculture. Seaweed growth requires nutrients, acquired from dissolved pools through their fronds, and light, and, as may also be density-dependent, but general relationships between seaweed growth, nutrient concentration and incident irradiance are not yet available. We used a dataset of 1729 experimental assessments of seaweed specific growth rates and density under various nutrient and irradiance levels retrieved from the published literature to examine the relationship between seaweed growth, density, irradiance and nutrient concentration. This analysis confirmed strong density-dependence of seaweed specific growth rates, and further confirmed that nutrient and irradiance limitation strongly impose density-dependent seaweed growth. These findings demonstrate that nutrient and irradiance limitation modulate density-dependent seaweed growth, and can help maximize growth rates in seaweed aquaculture, a rapidly growing component of global aquaculture production, by manipulating stocking density where nutrients are scarce and/or underwater light penetration poor.